2016
DOI: 10.1017/s0033291716002038
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serum anti-neuronal autoantibodies in patients admitted to acute psychiatric care

Abstract: NMDAR IgG autoantibodies, which are known to be strongly associated with anti-NMDAR encephalitis, were rarely found. CASPR2 and GAD65 antibodies were more frequently encountered in the present study than previously reported. Further research on the clinical significance of anti-neuronal autoantibodies in patients with acute psychiatric symptoms is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 43 publications
3
50
0
Order By: Relevance
“…Of the seven positive studies, four used a commercially available fixed cell-based assay (CBA) [10-12, 16], two used a live CBA [13, 15], and one used both, as well as a single molecule-based imaging method, for the sake of comparing approaches [14]. The majority of negative studies also used the same aforementioned commercially available CBA (or a modification of it) [17-22, 24-29], and four of these studies also included immunohistochemistry for further testing [19, 26-28]. Two negative studies, including one previously referenced study that also used the commercial CBA kit for testing some of its sample, used in-house CBAs [22, 23].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the seven positive studies, four used a commercially available fixed cell-based assay (CBA) [10-12, 16], two used a live CBA [13, 15], and one used both, as well as a single molecule-based imaging method, for the sake of comparing approaches [14]. The majority of negative studies also used the same aforementioned commercially available CBA (or a modification of it) [17-22, 24-29], and four of these studies also included immunohistochemistry for further testing [19, 26-28]. Two negative studies, including one previously referenced study that also used the commercial CBA kit for testing some of its sample, used in-house CBAs [22, 23].…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have also found immunoglobulin A (IgA) or immunoglobulin M (IgM) antibodies in a small proportion of patients (2.3–6.6%) [10-13, 24]; a finding of unknown clinical significance. These antibodies were also found in a small proportion of healthy controls (0.4–6.3%) in all but one of the studies that included a control group [10-12], further complicating interpretation of the results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations